Comparative assessment of Al2O3, CuO, and Al2O3-CuO Co-doping on the structural, optical, thermal, mechanical, and gamma-ray shielding properties of Bi2O3-B2O3-K2O glass system - Abely E. Mwakuna; C. Laxmikanth; K. Samatha; R.K.N.R. Manepalli (Next Materials)
This study compares the impact of Al2O3, CuO, and Al2O3-CuO co-doping on the structural, optical, thermal, mechanical, and gamma (γ)-ray shielding properties of the B2O3-Bi2O3-K2O (BBK) glass system. The glass samples were synthesized using the melt-quenching method, and their amorphous nature was confirmed through X-ray diffraction. Fourier-Transform Infrared spectroscopy identified key structural units, including BO3, BO4, AlO6, CuO4, and B-O-B linkages. Among the samples, the CuO-doped sample (BBK2) exhibited the highest density, followed by the Al2O3-CuO co-doped sample (BBK4), and the Al2O3-doped sample (BBK3), with the undoped sample (BBK) showing the lowest density. An inverse trend was observed for molar volume, which decreased as the boron-boron distance reduced. The oxygen packing density (OPD) was highest in BBK3 and lowest in BBK2. This difference arises from the replacement of boron by aluminium ions in BBK3, which enhances oxygen ion packing, whereas the presence of copper ions in BBK2 reduces the OPD. These findings highlight the distinct roles of Al2O3 and CuO in influencing structural packing, oxygen distribution, and network density. The optical band gap was highest in BBK3, followed by BBK1 and BBK4, with BBK2 exhibiting the lowest value. This trend is attributed to variations in the concentration of non-bridging oxygen sites, which influence the degree of depolymerization. BBK2 has a higher concentration of non-bridging oxygen sites compared to BBK3, leading to increased depolymerization and a reduced optical band gap. Glass transition temperatures (Tg), measured using Differential Scanning Calorimetry, followed the order: BBK1 < BBK2 < BBK4 < BBK3, with BBK3 showing the superior thermal stability. Mechanical properties, evaluated using the Makishima-Mackenzie theory, revealed that BBK4 exhibited the highest Poisson’s ratio, Young’s modulus, and shear modulus, followed by BBK3, BBK1, and BBK2. This trend is attributed to structural changes induced by the dopants. The γ-ray shielding properties, analyzed using Phy-X/PSD and XCOM software, showed that BBK2 had the best shielding performance, followed by BBK4, BBK3, and BBK1. Although BBK2 provides the most effective attenuation, BBK4 stands out as the preferred option, offering comparable shielding capabilities to BBK2, excellent mechanical properties, and thermal stability similar to BBK3, making it highly suitable for γ-ray shielding applications at 0.662 MeV, where both mechanical and thermal efficiency are critical.